Analisis Linguistik-Kontekstual atas Frasa ‘Ażāb Al-Khiz-y dalam Al-Qur’an: Perspektif Toshihiko Izutsu dan Fazlur Rahman - Saiful Millah; Arrazy Hasyim; Artani Hasbi (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2025)
The controversy that arises after a disaster occurs is whether it was punishment or not. The correlation between disaster and punishment can be concluded from two types of punishment in the Qur’an, first, the punishment in the world (al-‘ażāb al-adnā), and second, the punishment in the afterlife (al-‘ażāb al-akbar). One form of al-‘ażāb al-adnā is a natural disaster. The Qur’an also mentions the phrase ‘ażāb al-khiz-y which is related to the sentence fī al-ḥayāt ad-dunyā, so that is considered part of the punishment in the world. So far, there has not been a thematic interpretation study that focuses on discussing the term al-khiz-y and the phrase 'ażāb al-khiz-y, so it is necessary to be able to describe the meaning of the term as one of the characteristics of al-'ażāb. This qualitative research which focuses on verses in the Al-Qur’an containing the terms al-Khiz-y and ‘Ażāb al-Khiz-y based on Fazlur Rahman’s Double Movement theory and takes a semantic approach to the text of Al-Qur’an according to Toshihiko Izutsu. The primary data are the verses of the Qur'an that display the term al-khiz-y and the phrase 'ażāb al-khiz-y as well as the interpretations of the commentators in the classical and contemporary codification eras. The term al-khiz-y in the Al-Qur’an has three meanings : (1) al-faḍīḥah means humiliating; (2) al-‘uqūbah means punishment, sanction or retribution; and (3) al-‘ażāb means doom or torment. The disasters that occurred during the time of the Prophet Muhammad’s people until the end of time cannot be called punishment (al-‘ażāb), but only as world sanctions, retribution or punishment. The actualization of Allah’s Love (ar-Raḥmān) is more dominant than the Allah’s Power (al-'Azīz) towards the people of the Prophet Muhammad Saw.